Hadith #3410 - Sunan Abi Dawud - Ja'far bin Brqan جعفر بن برقان; Zayd bin Abi al-Zrqa'a زيد بن أبي الزرقاء يزيد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) conquered Khaibar, and stipulated that all the land, gold and silver would belong to him. The people of Khaibar said: we know the land more than you ; so give it to us on condition that you should have half of the produce and we would have the half. He then gave it to them on that condition. When the time of picking the fruits of the palm-trees came, he sent ‘Abd Allah b. Rawahah to them, and he assessed the among of the fruits of the palm-trees. This is what the p
Grade: Sahih

Hadith #3575 - Sunan Abi Dawud - Abdur Rahman bin Abi al-Zanad عبد الرحمن بن أبي الزناد; Abu al-Zanad أبو الزناد; ibn Abbas; Ibrahim bin Hamza bin Muhammad إبراهيم بن حمزة بن محمد; Ubaydullah bin 'Abdullah bin 'Utba عبيد الله بن عبد الله بن عتبة بن مسعود; Zayd bin Abi al-Zrqa'a زيد بن أبي الزرقاء يزيد (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone seeks the office of judge among Muslims till he gets it and his justice prevails over his tyranny, he will go to Paradise; but the man whose tyranny prevails over his justice will go to Hell.
Grade: Da'if